Presence of Pretrial in the Perspective of the Pancasila State of Law - Sahat Maruli Tua Situmeang (LAW REFORM, 2021)
Pretrial is a process that precedes a trial in court or a preliminary examination before entering a trial. However, in its application, pretrial institutions both before and after the Constitutional Court Decision Number 21/PUU-XII/2014 are not in accordance with the Criminal Procedure Code and also have weaknesses or shortcomings. This paper aims to find out the presence of pretrial institutions in the perspective of the Pancasila state of law. In other hand, pretrial institution as an institution that oversees the protection of the human rights of suspects/defendants is regulated in Chapter X Articles 77 to Article 83 of the Criminal Procedure Code. The determination of the suspect must be carried out carefully by taking into account the principle of presumption of innocence as a general principle in criminal procedural law that must be enforced by law enforcers. In law enforcement, of course, there must be supervision both vertically and horizontally so as to minimize the occurrence of irregularities. Therefore, it is important to establish an Ad Hoc institution as a substitute for a Pretrial institution in which the judges consisting of career judges, legal practitioners and academics can act whether there is an application or not which is filed by the suspect/defendant or his family or proxies so that the decision is objective. Thus, it is important to reformulate the Criminal Procedure Code regarding the determination of suspects.